TEKNIK PENILAIAN OBSERVASI DALAM PEMBELAJARAN SEJARAH DI MUSEUM UNTUK PESERTA DIDIK SEKOLAH DASAR - Fahruddin dan Gina Sari Yumna (Universitas PGRI Yogyakarta, 2020)
Abstract:This article aims to analyze historical learning in social science subjects by inviting elementary school students to learn outside the classroom. During this time the obstacles in learning history are verbalism, monotony, and lack of understanding of elementary school students about a historical event. Learning history can be maximized if elementary school students in addition to using book media, also use other media that contains educational elements and are in the local environment through observation in museums. The museum as a learning medium plays a role in providing concrete historical information to elementary school students. For teachers who apply observation-based history learning in museums need certain assessment techniques. The assessment rubric which consists of aspects of historical learning based on observation must be compiled by the teacher so that learning in the museum can be measured validly. Historical learning in museums with appropriate assessment techniques results in structured learning and high and valid learning achievements. Pembelajaran Sejarah, Museum, Observasi.Keywords: Museums, Historical Learning,Â Assessment Technique.